Kepuasan Hidup dan Pengaruhnya Terhadap Keberhasilan Pengobatan Penyakit Lupus - Ika Sandra Dewi; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Milna Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This study examines the relationship between life satisfaction and the effectiveness of systemic lupus erythematosus (SLE) treatment through a systematic review and meta-analysis of 32 studies (N=8,746) published between 2018 and 2023. The analysis reveals a moderate negative correlation between life satisfaction and lupus disease activity (r=-0.38, 95% CI: -0.44 to -0.32, p<0.001). More specifically, the data demonstrate a strong positive correlation between life satisfaction and quality of life in the context of health (r=0.52, 95% CI: 0.47-0.57, p<0.001) and a moderate positive correlation with medication adherence (r=0.34, 95% CI: 0.28-0.40, p<0.001). Longitudinal analysis (n=6 studies) shows that early improvements in life satisfaction are significantly predictive of reductions in lupus disease activity (?=-0.24, p<0.001) and enhancements in quality of life (?=0.29, p<0.001) over six months to 2 years. Meta-regression analysis further identifies age (?=0.008, p=0.03) and disease duration (?=0.015, p=0.01) as significant moderators of the effect of life satisfaction on SLE treatment outcomes. These findings extend previous research by Diener and Chan (2011) on well-being and health and by Mok et al. (2019) on depression in SLE by emphasizing the specific role of life satisfaction in SLE management. The novelty of this study lies in its focus on life satisfaction rather than solely negative risk factors, highlighting the potential for life satisfaction-based interventions in the management of SLE. This research supports the integration of life satisfaction assessments and psychosocial interventions into standard SLE care protocols, offering new insights into the psychoimmunological approach to SLE treatment.